The Critical Ear - Sara Pinheiro (Revista Vortex, 2024)
The “critical ear” is a concept crossing ideas of “technical listening” and “ear cleaning”. It was first presented as a workshop (Synth Library Prague, July 2024) dedicated to listening in its manifolds and complexities. It discussed our sonic environment and the several contexts in which listening takes place. Based on exercises that train frequency recognition, for example, how can we recognise that content in our mundane soundscape? In that sense, these exercises take a very pragmatic perspective, aiming at identifying frequencies and acoustic phenomena out-in-the-world. These comprise a basic relationship with sound, that of spatial acoustics, but at the same time, it adopts practices of deep listening and sound healing, towards the poetics of listening. The critical ear reflects the author’s practice endeavour: a constant sway between a technical understanding of sound and a socio-political reflection on being a listener.